ANALYSIS OF WEB PERFORMANCE FOR IMPROVEMENT RECOMMENDATION - Nusantara, Pualam Dipa (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2024)
Currently the use of web-based applications in various fields is increasing. This is because the benefits are very large especially to spread the information widely. Many area are using web-based application such as medical and health, advertizement, education, and also in the field of government, especially the KPUD in order to provide services to the community. In this research, an analysis on the performance of KPUD website of Central Java province where the result is recommendation for improvement of performance of Use of CDN and Mobile Speed from website.